Best Teach: A Social Media Inovation for Sekolah Best Agro International’s Teachers to Create A Better Education in Remote Areas - Saidah; Santoso, Sugeng (Cognitive Development Journal, 2023)
Best Agro International, a palm oil plantation company, runs a Corporate Social Responsibility (CSR) program in the education sector. This company have 28 schools of kindergarten level, 28 schools of elementary level, 12 schools of junior high school level and a school of vocational high school level, that built in the middle of the palm oil plantation spread across Central Kalimantan. Best Agro International ‘s educational CSR have many obstacles: the lack of interaction the teachers obtained from the outsides, many confusion and misconceptions about education system, and the space for the teachers to upgrade their skills is limited. This research purpose is to make an educational platform, namely Best Teach. The goal of this application is to provide a media for teachers to connect with each other, provide space for discussion and sharing of best practices, and help teachers to improve their educational competence. The design of this research is an explorative qualitative approach. This approach is used because it is in accordance with the data processing carried out, which does not use numerical analysis. Teach's research results are the right solution. With Best Teach, no more teachers are confused about implementing the curriculum, because they have space to share and discuss. This research contribution maximizes the competence and knowledge of Best Agro International School teachers, is also in accordance with curriculum demands, and is in line with Society 5.0 which requires humans to have creativity, critical thinking, communication and collaboration skills.